A promoted charge separation/transfer and surface plasmon resonance effect synergistically enhanced photocatalytic performance in Cu nanoparticles and single-atom Cu supported attapulgite/polymer carbon nitride photocatalyst. (December 2022) - Liu, Y.; Xu, L.; Zhang, N.; Wang, J.; Mu, X.; Wang, Y.
Abstract: The Cu nanoparticles and single-atom Cu-supported attapulgite/polymer carbon nitride (PCN) photocatalyst was successfully synthesized via a calcination process. The C≡N triple bond defect structure was successfully introduced into PCN structure through the composite process of modified attapulgite and PCN, suppressing the recombination of photogenerated electrons, narrowed the bandgap, and improved the efficiency of photocatalytic. The photoluminescence spectra, time-resolved fluorescence spectra, and ultraviolet-visible diffuse reflectance spectra together with theoretical calculation revealed that the doping of single-atom Cu further promoted the separation of photogenerated carriers and reduced the bandgap. The surface plasmon resonance effect produced by Cu nanoparticles and the promoted charge separation and transfer effect of single-atom Cu synergistically enhance the photocatalytic performance, and the degradation rate toward methylene blue dye was 7.7 times higher than that of PCN. Compared with the traditional single-method modified PCN catalyst, the catalyst prepared by this cocktail-like multi-composite strategy has the characteristics of high charge separation efficiency, high catalytic efficiency, and high stability. Graphical abstract: Image 1 Highlights: Cu nanoparticles and single-atom Cu-supported photocatalyst was synthesized. The C≡N triple bond was successfully introduced into polymer carbon nitride. The doping of Cu nanoparticles and single atom Cu enhanced the photocatalytic performance. Density functional theory calculations proved the doping of Cu enhanced the photocatalytic performance.